Make Rome Great Again: la Antigüedad como recurso en el contexto de la crisis y el nuevo giro derechizador - Machuca Prieto, Francisco (Historiografías, 2021)
This article examines how and why the Ancient World is once again becoming a source of political and cultural legitimation. More specifically, we pay attention to ancient Rome, idealized as a model and then used as an imperial paradigm in nonacademic realms, where an essentialist image of the past persists; which seems to respond to the recurring need for referents in the current context of systemic crisis. Simultaneously, we study the arguments that, closely linked to a new social shift to the right in many countries, use the Roman example to substantiate racist and xenophobic claims, all of this sometimes accompanied by an anti-scientific attitude.KeywordsRome, New Right, cultural wars, imperiofobia, ethnocentrism, racism.